Asthma research in Europe: a transformative agenda for innovation and competitiveness - Papadopoulos,NG; Androutsopoulou,A; Akdis,C; Dahlen,S-E; Djukanovic,R; Edwards,J; Garcia-Marcos,L; Johnston,SL; Kupczyk,M; Martin,TR; Myles,D; Palkonen,S; et al. (European Respiratory Journal, 2017)
Asthma is highly prevalent, often starting in infancy and persisting throughout life, and is associated with high morbidity and burden. It is a major global health challenge with growing impact, affecting more than 300 million people worldwide and at least 10% of all Europeans [1]. Furthermore, it is the most prevalent long-term condition in children [2]. Approximately 5–10% of asthma cases are so severe that current treatments do not work, and over five million people in the European Union (EU) fall into this category.People with asthma live at risk of life-threatening asthma attacks, leading to at least 500000 hospitalisations worldwide each year [3]. A European study estimated that unscheduled care and rescue medication accounted for 47% of the total cost-per-patient in infants, 45% in children and 56% in adults [4]. This results in high socio-economic impact, estimated at more than €70 billion annually [1]. This includes the costs of direct primary and hospital healthcare (estimated to be close to €20 billion per annum), costs due to lost productivity (€14 billion) [1], and the monetised value of disability-adjusted life-years (DALYs) lost (over €38 billion) [1]. Close to 1 million DALYs are lost due to asthma in Europe every year [5].Despite the fact that the direct and indirect costs of asthma are substantial and continue to rise, asthma remains under-prioritised in the EU research agenda. Only 0.5% of the Seventh Framework Programme (FP7) health research budget was devoted to asthma and chronic obstructive pulmonary disease (COPD) (€30million) [5]. In comparison, some 5.4 times this amount (over €163million) was spent on cardiovascular conditions and some 20.6 times (over €618million) on brain research.Asthma, with its high global prevalence and an associated multi-billion global market for treatments, plus its historical underfunding and the demand for new treatments and diagnostics, represents an enormous opportu